Women football observers’ experiences: a perspective from system justification and glass ceiling - Eratli Şirin, Yeliz; ÖZ, Günseli (Frontiers in Psychology, 2024)
Introduction The legitimization theory of the system explains that despite people’s inherent drive towards personal and group interests, they tend to support social systems. Understanding the sources of social pressure and the glass ceiling perceptions of female football observers is the main aim of this study in terms of examining attitudes within the legitimized system. To this end, the study sought to answer how female football observers are constructed in a marginalized position within the male-dominated football culture through sources of social pressure, and how they accommodate the acceptance of legitimizing the system despite encountering glass ceiling barriers in the context of Turkey. Method Data for the research were collected through in-depth individual interviews (9 female observers) using qualitative research methods. The collected data were analyzed using thematic analysis. After a comprehensive analysis of the interview transcripts, four themes emerged: Findings Gender-based positive and negative experiences; Glass Ceiling: Organizational Factors; Legitimization of Hierarchy-Reducing Myths; and Hope for Future Intragroup Progress within the Current System. Recommendations Our analysis reveals that female football observers, identified as match officials, indicate changes in authoritarian attitudes within recent institutional policies during their stadium experiences, characterized towards a more rational, female observer, and referee-focused stance. Additionally, entrenched stereotypes and legitimizing myths reducing hierarchy appear to generally establish legitimacy for female match officiating within the legitimization process. The research results suggest the importance for policymakers in the central referee committee in Turkey to consider the dimensions of legitimization both verbally and in writing when creating policies regarding women.